Apocalyptic COVID-19 mortality and BMI: a J-shape relationship? BMI and COVID-19 mortality - Lauretani, Fulvio; Lauretani, Ferdinando; Maggio, Marcello (Acta Biomedica Atenei Parmensis, 2022)
BMI could be considered the strongest key element for defining “frail/vulnerable” persons during SARS-COV-2 infection. National authorities should be taking into account these data for planning future preventive measured and vaccination and avoiding an increase of mortality due to COVID-19 infection. BMI is an expression of obesity and one of phenotypic criteria of undernutrition. Both of these conditions are really relevant worldwide, suggesting the need of implementing the knowledge on the importance of nutrition for general health and also for preventing severe forms of COVID-19 infection.